Ambient ozone and asthma hospital admissions in Texas: a time-series analysis - Julie E. Goodman; Ke Zu; Christine T. Loftus; Ge Tao; Xiaobin Liu; Sabine Lange (Asthma Research and Practice, 2017)
Abstract Background Many studies have evaluated associations between asthma emergency department (ED) visits, hospital admissions (HAs), and ambient ozone (O3) across the US, but not in Texas. We investigated the relationship between O3 and asthma HAs, and the potential impacts of outdoor pollen, respiratory infection HAs, and the start of the school year in Texas. Methods We obtained daily time-series data on asthma HAs and ambient O3 concentrations for Dallas, Houston, and Austin, Texas for the years 2003–2011. Relative risks (RRs) and 95% confidence intervals (CIs) of asthma HAs per 10-ppb increase in 8-h maximum O3 concentrations were estimated from Poisson generalized additive models and adjusted for temporal trends, meteorological factors, pollen, respiratory infection HAs, day of the week, and public holidays. We conducted a number of sensitivity analyses to assess model specification. Results We observed weak associations between total asthma HAs and O3 at lags of 1 day (RR10 ppb = 1.012, 95% CI: 1.004–1.021), 2 days (RR10 ppb = 1.011, 95% CI: 1.002–1.019), and 0–3 days (RR10 ppb = 1.017, 95% CI: 1.005–1.030). The associations were primarily observed in children aged 5–14 years (e.g., for O3 at lag 0–3 days, RR10 ppb = 1.037, 95% CI: 1.011–1.064), and null in individuals 15 years or older. The effect estimates did not change significantly with adjustment for pollen and respiratory infections, but they attenuated considerably and lost statistical significance when August and September data were excluded. A significant interaction between time around the start of the school year and O3 at lag 2 day was observed, with the associations with pediatric asthma HAs stronger in August and September (RR10 ppb = 1.040, 95% CI: 1.012–1.069) than in the rest of the year (October–July) (RR10 ppb = 1.006, 95% CI: 0.986–1.026). Conclusions We observed small but statistically significant positive associations between total and pediatric asthma HAs and short-term O3 exposure in Texas, especially in August and September. Further research is needed to determine how the start of school could modify the observed association between O3 and pediatric asthma HAs.